The right of small and medium-sized enterprises to positive discrimination in free market competition - Branko Korže (DANUBE: Law, Economics and Social Issues Review, 2019)
The author justifies the right of business entities to free economic initiative on the basis of the human right (hereinafter 'HR' or 'HRs') to liberty, and the right to positive discrimination of small and medium-sized enterprises (hereinafter 'SMEs') on the HR to equality, which is in the legal sense implemented by the HR to equal protection. Such positive discrimination ensures the equal protection of SMEs in the conditions of a free market (hereinafter 'FM') competition. Taking HRs as his starting points, the author discusses legal policy reasons that impose the duty to enact special measures in favour of SMEs on the legislature, and evaluates the legal sources in the Republic of Slovenia that regulate such measures. By means of the results obtained from a survey conducted with SMEs, the author examines the effects of measures to ensure the equal market position of SMEs, which in the conditions of economic globalisation enables a fair market game between SMEs and large enterprises, to ensure SMEs their existence and further development.
Keywords: 330; Free Market Competition; Human Right to Equality; Positive Discrimination; Small and Medium-Sized Enterprises; Social Market State